Apakah Model Pembelajaran Problem Solving Berbantuan Media Magic Spin Board Mampu Meningkatkan Literasi Sains? - Nikmah, Ernida Ainun; Masfuah, Siti; Utaminingsih, Sri (Universitas Muria Kudus, 2023)
Scientific literacy is one of the high-level abilities that is important for students, however, based on the results of PISA, Indonesia is in the top 10 of the bottom 10 out of 72 countries. The research aims to describe the application of problem solving models to improve scientific literacy with the help of magic spin board media. Research subjects IV SD 2 Rejosari with 20 students. The research method is Classroom Action Research and conducted in two cycles and two cycles were conducted in two meetings. This research finds improvement of the literacies, in the first cycle, the average percentage is 67.5%, good. It improves on second cycle into 79.12%, good category. good.. It can be concluded that the use of problem solving models assisted by magic spin board media can improve the scientific literacy of fourth grade students of SD 2 Rejosari